Teacher Certification Programs, Teacher Motivation And School Climate On Teacher Performance (Case Study : SMK Ibnu Aqil Bogor) - Koto, Andrias; Djamil, Masyhudzulhak; ., Indupurnahayu (Jurnal Manajemen, 2018)
The purpose of this study was to effect of teacher certification programs, teacher motivation and school climate on the performance of vocational teacher Ibnu Aqil Bogor. The research was conducted at the Vocational School of Ibn Aqil Bogor sample as many as 70 teachers. The research variables are teacher certification program, gur motivation and school climate as independent variables and teacher performance as the dependent variable. Data collection using questionnaires, interviews and observations. Data were analyzed descriptively and using simple linear regression analysis. The results showed the availability of teachers based on the quality of education is either minimal S1. 85.71% of teachers in vocational Ibn Aqil Bogor was educated S1. In terms of quantity of total 70 teachers filled out by the teacher labor fee of 20 people and the civil servant and teacher fixed foundation. Teacher certification programs, teacher motivation and school climate affects the quality of education by 58.2%, the remaining 41.8% is influenced by other factors.